2007
DOI: 10.1103/physrevb.76.144405
|View full text |Cite
|
Sign up to set email alerts
|

Multiple quantum NMR dynamics in dipolar ordered spin systems

Abstract: We investigate analytically and numerically the Multiple Quantum (MQ) NMR dynamics in systems of nuclear spins 1/2 coupled by the dipole-dipole interactions in the case of the dipolar ordered initial state. We suggest two different methods of MQ NMR. One of them is based on the measurement of the dipolar temperature in the quasi-equilibrium state which establishes after the time of order T2 after the MQ NMR experiment. The other method uses an additional resonance 45ˆ0-pulse after the preparation period of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…At the same time, this approach allows us to take into account the corrections due to the higher order terms of the averaged Hamiltonian theory [20], since these terms commute withÎ 2 as well. MQ NMR dynamics can be also investigated for systems with dipolar ordered initial state [21,22] by the suggested method.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this approach allows us to take into account the corrections due to the higher order terms of the averaged Hamiltonian theory [20], since these terms commute withÎ 2 as well. MQ NMR dynamics can be also investigated for systems with dipolar ordered initial state [21,22] by the suggested method.…”
Section: Discussionmentioning
confidence: 99%
“…In all these experiments the starting condition generally was the thermodynamic equilibrium in a strong external magnetic field (Zeeman order). The dipolar ordered state has also been considered as the initial state for numerical calculations of MQ experiments [20][21][22]. A method for encoding the coherence numbers of the dipolar-ordered state in a basis (X) orthogonal to the Zeeman (Z) basis (in the rotating frame) in solids was presented by H. Cho et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the growth of intensities of MQ coherence gets faster when the temperature decreases, and the intensities of multiple quantum coherences can be negative at low temperatures [16]. A few years later, it was proposed to use a so-called dipolar ordered state, a state in which nuclear spins are oriented along an internal local magnetic field [17], as the initial state in high temperature MQ NMR experiments [18] to faster form the correlations in spin systems [19,20]. As a matter of fact, it was found [19,20] that in experiments with the dipolar ordered state at high temperature the intensities of MQ coherences were several times higher than the analogous coherence in the standard MQ NMR experiment in which nuclear spins were oriented along an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%